WORLDVIEW AS A PERSPECTIVE IN STUDY OF SCIENCE AND RELIGION - Taqiyuddin, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2017)
Most secular studies still conclude that religion and science are not identical to each other. Western perspective sees that science was against religion because one of them is considered to inhibit the other. Philosophical elucidation was found the core problem lies in the basic assumptions and based on their respective definitions. As well as the characters and elements. Science is identical to observed facts, while religion is only connected to metaphysical matters. This background encourages the need for a revisionist study of the relationship between the two; bearing in mind, Islamic scientific traditions have historically placed both in the same position and intense dialogue. This study is a philosophical study using the literature method. The data analyzed is about the definitions and arguments about the worldview character in religion and science. The thematic content analysis produces that the right worldview can be a perspective that projects a meeting point between the two. This confirms that any scientific activities, even religious activities are based on different worldviews, and produce different assumptions and paradigms. The basis is the definition and character of each term.